Low skeletal muscle density is independently associated with cardiac valve calcification in dialysis patients - Li, Meng-Ting; Cao, Jing-Yuan; Li, Min; Zhao, Zhen; Mi, Jia-Run; Yang, Min; Zhang, Liu-Ping; Wang, Zi-Fan; Yu, Tian-Ke; Ju, Ping-Ping; Jiang, Yu-Jia; Wang, Yao; et al. (Frontiers in Physiology, 2025)
Assessing muscle characteristics is an emerging field for improving stratification of cardiovascular disease risks. However, the relationship between muscle characteristics and cardiac valve calcification (CVC) remains unclear. This study evaluated how muscle mass and muscle quality relate to the risk of CVC in dialysis patients. This study included dialysis patients from four centers in China who underwent chest computed tomography (CT) and echocardiography. Skeletal muscle index (SMI) and skeletal muscle density (SMD) were measured by opportunistic chest CT at the first lumbar vertebra level to assess muscle mass and muscle quality. Patients were categorized by calcified valves: no calcification, single-valve (aortic or mitral) calcification, and dual-valve calcification. Ordinal logistic regression assessed the relationships of SMI and SMD with CVC risk. Of 2,140 patients (mean age of 55 years, 58.8% male), 782 (36.5%) exhibited CVC: 550 (25.7%) with single-valve calcification, and 232 (10.8%) with dual-valve calcification. As SMD quartiles decreased, the ORs (95% CIs) for CVC consistently increased (1.22 [0.90–1.64], 1.46 [1.08–1.97], 1.49 [1.07–2.08]; P = 0.003) after adjusting for potential confounders. The OR (95% CI) for CVC associated with a 1 SD decrease in SMD was 1.20 (1.06–1.36; P = 0.004) in Model 3. Multivariable adjustments revealed no significant links between SMI and CVC risk. In this large multicenter study, we found that low SMD, but not low SMI, is independently associated with CVC in dialysis patients. Integrating SMD assessments into routine care may improve CVC management for this population.